Current situation of health workers' knowledge and practice on safe motherhood at public health facilities of Ninh Binh province in 2019 (Vietnam Journal of Community Medicine, 2021)
Objective: To assess knowledge and practices on safe motherhood of mothers giving birth at public health facilities of Ninh Binh province in 2019. Subjects: Health workers working at public health facilities of the province. Rearch method: Descriptive cross-sectional survey. Results:When asked about the danger signs of mothers after giving birth that need to be monitored, the highest percentage is prolonged bleeding (94.3%), the lowest is prolonged abdominal pain (70.7%). In full body examination, the percentage of health workers who  practiced correctly was found the lowest for cardiopulmonary examination (49.0%), breast examination (58.0%), and the highest for blood pressure measurement (91.7%). Conclusion: The rate of health workers having correct knowledge on safe motherhood was not high. The rate of health workers having correct practice on prenatal check-up steps and asking steps ranged from 68.2% to 94.3%.